2015
DOI: 10.3233/bmr-140527
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of low back pain during pregnancy

Abstract: Abstract. OBJECTIVES:This study investigated the self-reported prevalence and impact of low back pain (LBP) during pregnancy in primiparous and multiparous women, and their treatment-seeking rationales and experiences, including their use of physiotherapy. METHODS: A sample of 105 post-partum women was recruited. All participants answered a questionnaire; women who experienced LBP during pregnancy (n = 71) continue in the study and later they were also interviewed. Content analysis, descriptive and inferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 16 publications
8
63
2
10
Order By: Relevance
“…The fact that 80% of multiparous women with LBPP in the present study had a past history of LBPP in their previous pregnancy suggests that multiparous women generally have LBPP. However, the proportion of multiparous women with LBPP was not significantly different from the proportion of primiparous women with LBPP being in line with the results of previous studies (Mohseni-Bandpei et al, 2009;Mota et al, 2015). Mogren and Pohjanen (2005) reported that mean gestational age at the onset of LBPP was 22.1 weeks.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The fact that 80% of multiparous women with LBPP in the present study had a past history of LBPP in their previous pregnancy suggests that multiparous women generally have LBPP. However, the proportion of multiparous women with LBPP was not significantly different from the proportion of primiparous women with LBPP being in line with the results of previous studies (Mohseni-Bandpei et al, 2009;Mota et al, 2015). Mogren and Pohjanen (2005) reported that mean gestational age at the onset of LBPP was 22.1 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that increase in parity was associated with increased risk for lumbar pain and that risk for lumbar pain in multiparous women was higher than that in primiparous women (Mota et al, 2015). A past history of lumbar and pelvic pain related or unrelated to previous pregnancy (Kovacs et al, 2012), low educational level (Chang et al, 2011), and high body mass index (BMI) and overweight (Mogren and Pohjanen, 2005) have been reported to be as factors related to LBPP.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also have demonstrated that OMT is effective in improving low back pain during pregnancy. [9][10][11][12] Even though OMT is widely used for postpartum…”
Section: Methodsmentioning
confidence: 99%
“…Although pregnancy-related low back pain may be due to changes in ligament laxity and posture, there are several causes of low back pain during pregnancy, including lumbosacral disc herniation, musculoskeletal diseases, pregnancy-related osteoporosis, and sacral stress fractures [4,6]. In addition, studies have shown that pregnancy-related low back pain is associated with poor quality of life, sleep disturbances, and sick leave from work [1,3], but it is often accepted as a normal, painful process of pregnancy [3,7] because patients and clinicians have inadequate information about treatment options and fear of possible harmful effects of treatment on the developing fetus [1,3,5].…”
Section: Introductionmentioning
confidence: 99%